Global development finance: Harnessing cyclical gains for development - World Bank (Washington D.C. World Bank, 2004)
This publication is the annual review of recent trends in and prospects for financial flows to developing countries.
I: Analysis and summary tables
osa;6/9/16
Loans
Keywords: Development finance